Strategies to Improve Customer Satisfaction in Kusuma Persada Utama in Lamongan District (a Strategy to Increase Customer Satisfaction at PT. Kusuma Persada Utama in Lamongan Regency) - Dhita Dhora Damayanti (Enrichment : Journal of Management, 2020)
In Indonesia, it is certainly very modern, so that in recent years there have been many residential and property businesses. In this property and housing business in Indonesia, there are many types of houses to be traded. And the contractor's business is a company that is contracted or hired to carry out work projects based on the contents of the contract that he won from the project owner who is an agency or individual. The population in this study was taken from all customers of PT. Kusuma Persada Utama as many as 100 people. The sample used in this study were 50 respondents with the calculation of the Slovin formula.